Factors associated with near miss events of transfusion practice amongst doctors in Hospital Universiti Sains Malaysia - Joibi, Kimberly Fe (2020)
Introduction: A near miss in transfusion practice is defined as a deviation from standard procedures, discovered before transfusion and has the potential to lead to a transfusion error. Near miss investigation is vital to prevent future occurrences. Unpublished yearly audit of our centre showed that house officers were often involved in near miss events. Objectives: This study aims to identify the common causes and associated factors of near miss events amongst doctors in Hospital USM. Methodology: The first part of this study is a cross-sectional study which required the data collection from all requests for Group, Screen and Hold (GSH) and Group and Crossmatch (GXM) tests sent to Transfusion Medicine Unit Hospital USM from 2011 until 2017. Second part is a case-control study which analyses the association of sociodemographic, workplace and experience factors with near miss events amongst house officers (HO) using logistic regression. Case group included 42 HO involved in near miss and control group consisted of 124 randomly selected HO who sent requests to our unit and were not involved in near miss. Results: We reported 83 near miss events among 242 004 GSH and GXM requests with a prevalence of 0.034 % (CI, 0.027% - 0.042%). Rate of near miss events were one event for every 2916 requests. Mean reporting rate was 11.9 events per year. Clinical near miss predominates with 89.2% over laboratory near miss of 10.8% from total near miss. Mislabelled events (33.7%) were more than miscollected events (10.8%). HO were involved with most events (83.1%). Most events occurred in Medical and Obstetrics and Gynaecology wards with 26 cases (31.3%) each. We found a significant association between the age of HO with near miss events. HO who are a year older decrease the odds of having a near miss event by 30% (CI, 0.51 - 0.96). Conclusion: The prevalence of near miss events in our centre were relatively low. However, the consequences if a near miss goes undetected are detrimental to the patient. Our study has shown among areas for improvement include improving sampling practices in clinical areas, adequate training of laboratory technicians and providing proper transfusion education to house officers.